1991
DOI: 10.1002/aja.1001920105
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic and histochemical studies of the mononuclear osteoclast of the mouse

Abstract: Osteoclasts collected from the long bones of mice were cultured on dentin slices. To identify osteoclasts, the tartrate-resistant acid phosphatase (TRACPase) activity of cultured cells was histochemically examined by the azo dye method. The TRACPase-positive cells could be distinguished from other cells by light microscopy. The cells were sectioned by alternating semithin and ultrathin sections to observe their ultrastructure and three-dimensional structure. TRACPase activity was detected both in multi-nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…Abundant lysosomal vacuoles were also observed in mononuclear osteoclast precursor cells (Baron et al, 1986;Domon and Wakita, 1991). Furthermore, coated pits and coated patches described in mononuclear precursors of osteoclasts in a rat model (Baron et al, 1986) were also observed in our cells.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Abundant lysosomal vacuoles were also observed in mononuclear osteoclast precursor cells (Baron et al, 1986;Domon and Wakita, 1991). Furthermore, coated pits and coated patches described in mononuclear precursors of osteoclasts in a rat model (Baron et al, 1986) were also observed in our cells.…”
supporting
confidence: 65%
“…Our cells cultured with 0-CSF showed a striking resemblance to cells described by Domon and Wakita (1991) in their studies of cultured bone marrow mononuclear cells. The TRAPase-positive cells in our study, however, were derived from bone marrow progenitors that had the capacity to proliferate and form colonies in response to 0-CSF after 14-day incubation; thus, they must be derived from much earlier precursors than the preosteoclasts studied by Domon and Wakita in their 3-day culture experiments.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…These reports disregarded the presence of mononuclear osteoclasts which were observed in serial sections based on criteria of both acid phosphatase activity and resorptive lacunae (Kaye, 1984) or odontoclasts because their presence was not proven precisely. Previously, we have demonstrated the presence of mononuclear osteoclasts with ruffled borders in vitro (Domon and Wakita, 1991) and mononuclear odontoclasts in vivo (Domon et al, 1994), and investigated the distribution of number of nuclei per human odontoclast, and reported that 93.8% of cells had 10 or fewer, including mononucleus (Domon et al, 1997). These reports indicate that the distribution of nuclei in osteoclasts or odontoclasts varies little in mammals.…”
Section: Introductionmentioning
confidence: 91%
“…Since the number of multinucleated cells was similar in control and experimental 7-day cultures, the effects of both substances were very likely to increase the intrinsic cellular resorption activity. We cannot however, exclude the possibility that VD3 and HILDA/LIF increased the number of mononuclear TRAP-positive cells which possess osteoclastic activity [12,34]. The scoring of these cells in 7-day cultures was very difficult.…”
Section: Discussionmentioning
confidence: 99%